Detection of fetal malnutrition and its associated maternal factors in a rural setting - Janardhan, Alok M.; Alok, Sandhya; Janardhan, Leelavathi (International Journal of Contemporary Pediatrics, 2020)
Background: The objectives of study were to analyse and compare the methods for detection of fetal malnutrition and to study the maternal factors associated with fetal malnutrition in babies born in rural hospitals. Methods: Periodic prospective cross-sectional case-control questionnaire-based study. Nursing home and Hospital based in rural population from January 2017-March 2018. There were 350 term newborns born in Shrinivasa Nursing Home, and Crawford General Hospital, Sakleshpur, were selected consecutively. Inclusion criteria: live, singleton term neonates. Exclusion criteria: Preterms, post-terms, those with congenital malformation, multiple gestations, cephalhematoma, subgaleal bleed. Anthropometry, fetal malnutrition assessed using clinical assessment of nutrition (CAN) score, Ponderal and Kanawati indices between 24–48 hours of birth. Newborns with fetal malnutrition (cases), and well-nourished babies (controls) assessed for maternal risk factors using standardised questionnaire from mothers. Results: CAN score identified 185 (52.9%) as malnourished and 165 (47.1%) as normal; Ponderal index classified 170(48.6%) as malnourished and 180 (51.4%) normal. Kanawati index grouped 151 (43.1%) as malnourished. Maternal factors: age (91.7% among <20 yr mothers-malnourished, 25% among >35 yrs), socioeconomic status (status 3, 4 had 57.2%, 66.7% malnourishment), improper antenatal care(80.7% irregulars; 38.5% among regulars), primiparity (60%;against 38.3% among multipara), pre-eclampsia (78.7%; 41.3% in normotensives), anemia (55.4%), weight gain (83.2% in <10 kg; 33.33% in >10 kg), stature (73.5% in <145 cm; 39.7% in >145 cm), medical illness (55.81%). Conclusions: CAN score is simple, systematic, clinical method of identifying malnutrition; statistically superior as screening tool. Maternal factors: improper antenatal checkups, primiparity, pre-eclampsia, medical illness, inadequate weight gain, short stature had significant association with fetal malnutrition. Maternal age, socioeconomic status, anemia not statistically significant.